Electroconductive hyaluronic acid/gelatin/poly(ethylene oxide) polymeric film reinforced by reduced graphene oxide - ALEMDAR YAYLA, NESLİHAN (WILEY, 2019)
Novel electroconductive polymeric films with enhanced mechanical performance were fabricated by encapsulating reduced graphene oxide (RGO) at different concentrations (0-50 vol %) into a hyaluronic acid/gelatin/poly(ethylene oxide) (HyA/Gel/PEO) polymeric structure. The obtained RGO-reinforced polymeric films were characterized by Fourier transform infrared and scanning electron microscopy analyses. Mechanical performances were measured with a universal mechanical testing machine. The results verified that the RGO reinforcement significantly enhanced the mechanical performances of the films. To determine the biocompatibility of the polymeric films, L929 (murine fibroblast) cell lines were used. The water uptake capacities were measured using swelling tests. A four-probe method was used to measure conductivity characteristics. The conductivity results indicated that HyA/Gel/PEO film containing 20 vol % RGO has the highest average electrical conductivity (1.832 x 10(-6) S/cm). All of the results demonstrated that the obtained electroconductive films could be used in biomedical fields in the future, especially in controlled drug release systems and tissue engineering. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 46905.
Keywords: conducting polymers; films; mechanical properties; DRUG-DELIVERY; MECHANICAL-PROPERTIES; HYBRID SCAFFOLDS; COMPOSITE FILMS; ACID; FABRICATION; HYDROGELS; STABILITY